Analisis Usaha Pembuatan Tahu (Studi Kasus pada Pabrik Tahu “Berkat Sekumpul” Martapura) - Fitriani Fitriani; Ana Zuraida; Siti Erlina (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
The study aims to determine the feasibility (RCR) and the break-even point (BEP) of tofu making business. The method used is a case study on "Berkat Sekumpul" company in Martapura. The study was conducted for 6 (six) months starting from October 2012 to March 2013. The results showed the business is feasible, the RCR is 1.13 and break even on sales of 4,902 sheet at a price on Rp 51,260 per sheet, - or return on Rp 25,275,000,-